2021
DOI: 10.1136/annrheumdis-2021-219951
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of two adalimumab biosimilars in 1318 real-world patients with inflammatory rheumatic disease mandated to switch from originator adalimumab: nationwide observational study emulating a randomised clinical trial

Abstract: Objectives In 2018, a nationwide mandatory switch from originator to biosimilar adalimumab was conducted in Denmark. The available biosimilar was GP2017 (Hyrimoz) in Eastern regions and SB5 (Imraldi) in Western regions. We aimed to assess the comparative effectiveness of GP2017 versus SB5 in patients with rheumatoid arthritis (RA)/psoriatic arthritis (PsA)/axial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 37 publications
2
30
0
1
Order By: Relevance
“…Our results highlight the overall good drug persistence of ABP 501 in both inflammatory arthritides patients who are naïve and experienced to ADA. In particular, ABP 501 patients switching from originator to biosimilar showed a high retention rate that was comparable to the ones reported for other ADA biosimilars such as GP2017 and SB5 [ 17 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our results highlight the overall good drug persistence of ABP 501 in both inflammatory arthritides patients who are naïve and experienced to ADA. In particular, ABP 501 patients switching from originator to biosimilar showed a high retention rate that was comparable to the ones reported for other ADA biosimilars such as GP2017 and SB5 [ 17 ].…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, patients switching from originator ADA to ABP 501 showed a lower risk of treatment discontinuation. Observational data on both other ADA biosimilars such as GP2017 and SB5 [ 17 , 25 ] and other TNFi biosimilars [ 26 , 27 , 28 , 29 , 30 ] showed that switching from originator to biosimilar was tolerated generally well. The only other factor associated with a negative effect on drug survival in our cohort of patients was the year of ADA prescription.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Other data from the DANBIO registry on a non-medical switch from originator to two different adalimumab (ADA) bsDMARDs (GP2017 versus SB5) also showed a high retention rate of 89.5% at year 1. 14 This head-to-head comparison of two different bsDMARD was possible because of different results of price negotiations in two regions of Denmark. Interestingly, the estimated risk of withdrawal was lower for GP2017 compared with SB5 [hazard ratio (HR): 0.60; 95% CI: 0.42 to 0.86], and the 6-month remission rate was also higher [odds ratio (OR): 1.72; 95% CI: 1.25 to 2.37].…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 6 , 11 , 32 Biosimilars are increasingly used in routine care of patients with RA. 33 However, the uptake of biosimilars has varied considerably between countries. 34 Randomized clinical trials (RCTs) and real-world data are crucial to improving physician and patient confidence in these medicines.…”
Section: Introductionmentioning
confidence: 99%